Analisis Kinerja Keuangan Berdasarkan Metode Economic Value Added (EVA) Pada PT. Xl Axiata Tbk. - Irna Febryanti; Aris Munandar; Juwani Juwani (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The Economic Value Added (EVA) method is very important in assessing financial performance comprehensively because it considers the cost of capital and measures the actual added value for shareholders. The purpose of this study is to determine financial performance based on the Economic Value Added (EVA) method at PT. Xl Axiata Tbk. This type of research is descriptive quantitative with a list of ratio tables as research instruments. The research population is for 18 years with a research sample for 10 years using the purposive sampling method. Data collection techniques use documentation and literature studies. Data analysis techniques use Economic Value Added analysis, descriptive analysis and t-test. The results of the study show that the financial performance of PT XL Axiata Tbk, based on the EVA method, is not optimal in creating sustainable economic added value. This is indicated by the EVA value which is always negative (EVA <0) every year.